Equita’ e reciprocita’ fra Ancien Régime e societa’ contemporanea - Levi, Giovanni (ENDOXA, 2002)
The principies of reciprocity as they opérate during the Anden Régime need to be un of an unequal but equitatíve society. The society was fair according to the principies of distributive justice: to everyone according to his social status. In this way, taking the concepts of equity and reciprocity as its starting point of discussion the author enquiries about the rising of the formally equalitarian modem societies.